TERAPI TERKINI MULTIPLE MYELOMA - Suega, Ketut; Sripurnama Sjah, Yunny (journal of internal medicine, 2009)
Management strategies for Multiple Myeloma (MM) have continued to evolve as the result of innovative treatmentmodalities and efÞ cacy data used in establishing new standard of care. In 2004, multiple myeloma was diagnosed in more than15.000 people in the United States and will account for approximately 20% of deaths due to hematologic malignancies. Mostcommonly diagnosed in the growing elderly population.Until recently, few effective treatment existed. The use of alkylating agents and corticosteroid had remained the treatmentof choice for almost four decades. On a cellular level, the disease is characterized by complex interactions between tumor cellsand the surrounding bone marrow microenvironment. Understanding of the relationship between malignant plasma cells andthe microenvironment has sparked ongoing efforts to develop targeted therapeutic agents for treatment of this disease. Recentadvances in its treatment including using of the immunomodulatory drugs such as thalidomide and lenalidomide as well as theproteasome inhibitor bortezomib. Each of these agents is undergoing extensive clinical evaluation in combination with othertherapies to produce unprecedented response rates in newly diagnosed and relapsed MM. They have each improved the responseto therapy, but they are expensive. In recent years, evidence supporting a survival beneÞ t for three new drugs have resulted intheir inclusion, in combination with older drugs, in the management of younger and older patients. Each of these new drugs hasmultiple mechanisms of action, targeting both intracellular signaling pathways and tumor microenvironment. This review focuson the newer agents such as thalidomide, bortezomib, and lenalidomide in treatment of patient with newly diagnosed MM andrelapsed MM, treatment-related side effect, and future using of these agent including new combination therapy